Determining the sex of equine fetuses: an update. Issue 1 (23rd January 2019) - Neal, Huw
Abstract : Knowing whether a pregnant mare is carrying either a colt or a filly fetus is helpful for many breeders, both for commercial and private purposes. This information may influence future mating plans for the mare and valuations for insurance, and may contribute to a decision regarding possible sale of the animal. The stage of pregnancy at which fetal sex is most easily identified, especially for new examiners, is the early period of development when the primitive external genital tissue can be recognised relatively easily with a clear difference between male and female forms. This article describes the development of the equine embryo, the anatomy of the fetus in the early stages of pregnancy and the ultrasonographic approach required to determine the sex of the fetus.